Waste banks as social movements: a case study of Morse Indah waste bank in Banjarmasin - Samsir Eka Putera; Muhammad Gagah Dirgantara; Lannie Marseli Faderi; Entry Welny Sitindaon; Alissa Dian Bratajaya; Muhammad Farisan Kasyfi; Ni'mah Ni'mah (Priviet Social Sciences Journal, 2026)
Waste banks have commonly been examined as tools for environmental education, community empowerment, and urban waste management programs. However, their role as social movements that mobilize collective action and shape everyday environmental practices at the community level remains underexplored. This study addresses this gap by analyzing the Morse Indah Waste Bank in Banjarmasin through the perspectives of Resource Mobilization Theory (RMT) and New Social Movement (NSM). This research employs a descriptive qualitative approach with a single case study design. Data were collected through a semi-structured interview with the key actors of the Morse Indah Waste Bank, non-participant observation of routine activities, and document analysis of relevant policy and institutional materials. The data were analyzed using qualitative content analysis through inductive and deductive coding, supported by triangulation across interviews, observations, and documents. The findings indicate that the Morse Indah Waste Bank functions as a community-based cultural social movement rather than a contentious political movement. Resource mobilization occurs through active commitment, recyclable materials, limited financial incentives, and cross-sector networks involving local governments and corporate social responsibility programs. From the NSM perspective, the initiative emphasizes collective identity formation and cultural change, reflected in routine practices such as waste sorting, regular waste deposits, and environmentally oriented lifestyles. Nevertheless, the sustainability of the movement remains constrained by fluctuating community participation and strong dependence on a small number of key actors. This study contributes to the social movement and community-based environmental governance literature by demonstrating how waste banks can operate as cultural social movements at the neighborhood level while also revealing organizational vulnerabilities that shape their long-term sustainability.